Distributions of topological observables in inclusive three- and four-jet events in pp collisions at root s=7 TeV - Khachatryan, V. (2015)
This paper presents distributions of topological observables in inclusive three- and four-jet events produced in pp collisions at a centre-of-mass energy of 7 TeV with a data sample collected by the CMS experiment corresponding to a luminosity of 5.1 fb(-1). The distributions are corrected for detector effects, and compared with several event generators based on two- and multi-parton matrix elements at leading order. Among the considered calculations, MadGraph interfaced with PYTHIA6 displays the overall best agreement with data.